2013
DOI: 10.1007/s10900-013-9799-1
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Use and Prescription Access Among Uninsured Patients Managing Chronic Diseases

Abstract: Effective chronic condition management is dependent upon prescription medication access and compliance. Impacted access results in increased pain, worsening of the condition and association of additional health-related problems. Prescription medication costs constitute a significant burden for patients who are uninsured and managing chronic conditions. This burden links to the likelihood of medication non-compliance. The purpose of this research was to test the ability of the Andersen Behavioral Model of Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Ultimately, the BMHSU postulates that need factors are the most immediate causal factor influencing a patient's decision to enroll and use health services. The BMHSU has been used as a framework to: 1) understand how and why uninsured patients with chronic disease use hospital services and medications; 35 2) explore relationships between use of health care services among medically underserved and uninsured patients living with chronic disease; 36 and …”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, the BMHSU postulates that need factors are the most immediate causal factor influencing a patient's decision to enroll and use health services. The BMHSU has been used as a framework to: 1) understand how and why uninsured patients with chronic disease use hospital services and medications; 35 2) explore relationships between use of health care services among medically underserved and uninsured patients living with chronic disease; 36 and …”
Section: Introductionmentioning
confidence: 99%
“…Our findings also indicate that uninsured or low-income individuals with vestibular vertigo had significant difficulty accessing specialty care and prescription medications, with higher odds of skipping, taking less, and delaying filling prescriptions due to financial constraints. This is concerning as lack of access to prescription medications has been associated with increased risk of additional health problems and worsening of the condition that is being undertreated (Goodman Shepherd et al 2014). The management of many causes of vestibular vertigo including Meniere’s disease, vestibular migraine, and benign paroxysmal positional vertigo includes medications, specialist care (e.g., vestibular physical therapy), and/or additional follow-up (Kinney et al 1997; Agrawal et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been limited studies conducted in FQHC patients with asthma to assess medication use, our study findings align with previous research. Shepherd et al 32 found that 38% of patients with chronic diseases in an FQHC were unable to fill their medications because they could not afford them. Cost-related barriers to access prescription medications have shown to negatively affect patients’ adherence to medications and health outcomes, including asthma control and quality of life.…”
Section: Discussionmentioning
confidence: 99%